Pengaruh Model Pembelajaran Flipped Classroom Terhadap Hasil Belajar Kognitif Peserta Didik SMAN 44 Jakarta - Angga Alviansyach; Aris Munandar; Sony Nugratma Hijrawadi (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
Indonesia's ranking in the Program for International Student Assessment (PISA) is always decreasing and the problem in the world of Indonesian education is that teachers have not been able to choose, maximize and implement learning models as adaptive learning techniques wisely. This learning pattern must be changed to focus on students (student center). This research aims to determine the effect of the flipped class learning model on the cognitive learning outcomes of students at SMAN 44 Jakarta. The method used is quantitative with an experimental approach. Data collection at SMAN 44 Jakarta, with students at class XI level. For class XI IPS 1 as an experimental class using the flipped class learning model and class XI IPS 3 as a control class using a conventional learning model. The data obtained came from pre-test and post-test scores with a data collection period of 3 meetings. Test the pre-requisites for data analysis using normality and homogeneity tests. The data analysis technique used in this research is the Independent Sample T-Test. The results show that there is a significant influence on the average learning outcomes of students in the experimental class from 39.44 to 75.27, while for the control class the score was 38.47 to 63.47. The conclusion of this research is that there is an influence in using the flipped class learning model.